Complicated cases in foreign bodies of the ear, nose, and throat: a case series (Colombia Medica, 2024)
Background: Managing foreign bodies in otorhinolaryngology requires appropriate treatment based on case severity.Objective: To analyze the clinical characteristics associated with complicated cases of foreign bodies.Methods: This study categorized patients with diagnosed foreign bodies into complicated and uncomplicated cases. Complicated cases were defined as complications from foreign bodies requiring an operating room procedure, hospitalization, or tracheal foreign body. Otherwise, they were considered uncomplicated. Clinical data and disease variables were recorded. Univariate and multivariate regression analyses were performed to evaluate the significance of different clinical features between the groups (p-value